Language Teachers' Emergency Remote Teaching Experiences During the COVID-19 Confinement - Catalina Juárez-Díaz; Moisés Perales (Universidad Nacional de Colombia, 2021)
This study describes 26 English language teaching faculty members' and 32 preservice English as a foreign language teachers' emergency remote teaching experiences and emotions. Verbal data gathered through an online questionnaire with open questions were analyzed using semidirected content analysis. Most faculty and all students reported negative feelings, which were connected with some faculty members' focus on delivering content without interaction and with insufficient Internet access. Some students' autonomy allowed them to overcome the first of these challenges. Teachers with online education training reported better experiences. Thus, universities and the State must provide more training and equipment to close the digital gap and ensure effective emergency remote teaching.